1206 Neonatal complications of SARS-CoV-2 infection in the UK: a prospective national cohort study using active surveillance. (17th August 2022) - Ali, Shohaib; Morelli, Alessandra; Placzek, Anna; Hurd, Madeleine; Doherty, Cora; Sharkey, Don; Mactier, Helen; Ladhani, Shamez; Draper, Elizabeth; Quigley, Maria; Kurinczuk, Jenny; Knight, Marian; et al.
Abstract : Aims: While there were no neonatal deaths recorded from SARS-CoV-2 infection in the first pandemic year, there is little known about the differing impacts new variants have on neonatal populations. We set to describe the neonatal complications across three periods corresponding to the dominant SARS-CoV-2 variant in the UK: 1 March 2020 to 30 November 2020 ('wildtype'), 1 December 2020 to 15 May 2021 (Alpha), and 16 May 2021 to 15 December 2021 (Delta). Methods: From 1st March 2020 to the 15th December 2021 prospective neonatal data collection of hospitalised neonates with SARS-CoV-2 infection and babies born to mothers with COVID-19 and admitted for neonatal care was undertaken through the British Paediatric Surveillance Unit (BPSU). 1 From 1st March 2020 the UK Obstetric Surveillance System (UKOSS) 2, 3 prospectively collected information about all pregnant women admitted to hospital with confirmed SARS-CoV-2. Both studies were adopted as urgent public health priority studies. Neonatal deaths were attributed directly to SARS-CoV-2 if the treating paediatrician reported that SARS-CoV-2 contributed to the baby's death, and attributed indirectly if maternal SARS-CoV-2 infection was reported to have contributed to neonatal death (e.g. extreme preterm birth). Results: 836 BPSU cases notified during the study period. Complete data forms were available for 703 (84%) individual babies. Of these, 276 had confirmed SARS-CoV-2 infection. The weekly number of neonates admitted with confirmed SARS-CoV-2 by date of diagnosis is shown in figure 1 . During the surveillance period: 9/268 (3%) were born <28 weeks gestational age, 33/268 (12%) 28-31 weeks, 64/268 (23%) 32-36 weeks, and 162/268 (59%) ≥37 weeks. Gestational data were missing for 8 (3%) babies 182/251 babies (66%) were of white ethnicity, 47/251 (17%) Asian/British Asian, 18/251 (7%) 11 (4%) Black/Caribbean/African/Black British, 11/251 (4%) mixed, 3/251 (1%) other. Ethnicity data were missing for 15 (3%) of babies. 223 (81%) neonates were discharged home, 13 (5%) were transferred, and 7 babies had SARS-CoV-2 infection and died. Four of the deaths of babies who were born during the delta wave were directly attributable to SARS-CoV-2. Neonatal mortality in association with SARS-CoV-2 infection is described in table 1 . Conclusion: Using population level surveillance data we describe neonatal complications directly and indirectly attributable to SARS-CoV-2 infection during the first three pandemic waves. This study demonstrates the low risk to neonates despite the emergence of new variants. Continued surveillance will allow the impacts of new variants on the neonatal population to be characterised. References: Gale C, Quigley MA, Placzek A, et al . Characteristics and outcomes of neonatal SARS-CoV-2 infection in the UK: a prospective national cohort study using active surveillance. Lancet Child Adolesc Heal 2021;5 :113–21. Vousden N, Ramakrishnan R, Bunch K, et al . Impact of SARS-CoV-2 variant on the severity of maternal infection and perinatal outcomes: Data from the UK Obstetric Surveillance System national cohort. Medrvix 2021. doi:10.1101/2021.07.22.21261000. Knight M, Kurinczuk JJ, Tuffnell D, Brocklehurst P. The UK Obstetric Surveillance System for raredisorders of pregnancy. BJOG An Int J Obstet Gynaecol 2005;112 :263–5.